INVESTIGATING THE FEASIBILITY OF PHASE INTERFEROMETER BASED ON MULTI-ANTENNA FOR 2D DIRECTION FINDING - Rizos, C (International Journal of Allied Sciences (IJAS), 2022)
In the radio direction finding system, direction finding methods of Phase Interferometer have been widely applied, but because of its direction finding ambiguity, there is a contradiction between direction finding range and direction finding accuracy. In order to relieve the contradiction, multi-baseline phase interferometer is generally used to measure angles. However, this method is mainly aimed at one-dimensional angle measurement, so its system utilization is low. Therefore, a phase interferometer based on multiple antennas is proposed in this paper to measure the angle of pitch and azimuth in two dimensions, and the dual-baseline ambiguity resolution method is used to improve the accuracy of pitching angle measurement. Finally, the simulation results indicated that the theoretical analysis was correct.